(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
PRP therapy is now widely used in modern medicine in the complex treatment of many different diseases. This method is based on the biostimulation properties of a large number of saturated platelet of the autoplasm of the tumor and stimulates the growth factor of the host cells to restorate the damaged tissue. PRP (platelet-rich plasma) therapy is a treatment method that involves reintroducing plasma that has been separated from the patient’s blood into the patient’s body. The composition of plasma is rich in a large number of thrombocytes and growth factors, and it is now widely used in various medical fields, such as dermatology, traumatology, reproductive medicine, urology, microvinargen, aesthetic medicine and more. According to the results of the scientific review published on the Pubmed website in 2020, the main mechanisms of action of PRP therapy were shown. According to him, plasma contains 5-6 times more platelets than blood, and platelets have the ability to produce growth factor, which is important in tissue regeneration. Because platelets contain a high concentration of growth factor, they have anti-inflammatory, immunomodulatory and regenerative effects and futher shorten the rehabilitation period (Peter Events, Kentaro Onishi and other authors, 2020).